Impacts of hydro-climatic trends and upstream water management on hydropower generation at the Bagré dam. Issue 6 (19th May 2022) - Yangouliba, Gnibga Issoufou; Koch, Hagen; Liersch, Stefan; Sintondji, Luc Ollivier; Sidibé, Moussa; Larbi, Isaac; Limantol, Andrew Manoba; Yira, Yacouba; Dipama, Jean-Marie; Kwawuvi, Daniel
Abstract: Global hydro-climatic trends are ambiguous, challenging the management of water resources. This challenge is addressed in the current study by investigating the impacts of hydro-climatic trends and upstream water management on hydropower generation at the Bagré dam. Modified Mann–Kendall trend test, Standard Normal Homogeneity Test and Pettit test were applied to some selected hydro-climatic variables for the trend and the change year detection, whereas the relationship between upstream dam management, hydro-climatic variables and hydropower were assessed through the Spearman correlation. The results revealed an annual positive trend for all hydro-climatic variables except for water level, lake evaporation and outflow. The break years observed in hydropower generation (2002) and inflow (2006) were mainly due to the construction of the Ziga dam in 2000 and its management change in 2005, respectively. The study also showed that hydropower generation declines each May (−30.36 MWh) and June (−16.82 MWh) due to the significant increase in irrigation withdrawals (1.94 hm 3 in May and 0.67 hm 3 in June). The results of this study highlighted the non-linearity in the relationship between hydropower generation and hydro-climatic variables as none of the correlation coefficients (apart from turbine) are very strong (>0.8). As many human activities occurred in the basin, further research should be focused on the use of semi-distributed models to assess the impacts of water-use and land-use change on hydropower generation. HIGHLIGHTS: All hydro-climatic variables increased significantly except water level, lake evaporation and outflow. The construction of the Ziga dam in 2000 led to a significant increase in annual hydropower generation at Bagré dam from 2002. The change in management of the Ziga dam in 2005 led to a significant increase in annual inflow at Bagré dam from 2006. All the months of the year experienced an increasing trend of hydropower generation except May and June. The decline of hydropower generation in May and June is the consequence of the increase of water withdrawals for irrigation.